Roles of Novel Reactive Cationic Copolymers of 3-Chloro-2-hydroxypropylmethyldiallylammonium Chloride and Dimethyldiallylammonium Chloride in Fixing Anionic Dyes on Cotton Fabric - Yikai Yu; Yuejun Zhang (Journal of Chemistry)
The roles of novel reactive cationic copolymers (P(CMDA-DMDAAC)s) of 3-chloro-2-hydroxypropylmethyldiallylammonium chloride (CMDA) and dimethyldiallylammonium chloride (DMDAAC) in fixing anionic dyes on cotton fabric were studied by modern instrumental analysis technologies such as FT-IR spectra and SEM analysis, to achieve the new theoretical guides for the wide applications of those dye fixatives. The FT-IR spectra of the obtained insoluble-water color lakes verified that they could be formed from the electrostatic interactions of the P(CMDA-DMDAAC)s with anionic dyes, which were further confirmed by the FT-IR analysis of the anionic dyes on dyeing cotton sample fixed by P(CMDA-DMDAAC)s. The FT-IR spectra of cotton samples fixed by P(CMDA-DMDAAC)s showed the absorptions of P(CMDA-DMDAAC)s and the signs similar to the formation of new ether linkage on cotton fabric even after being repeatedly washed, which were further confirmed by the SEM analysis of the fixed dyeing cotton samples. Thus, the reactive units (CMDA) of the obtained P(CMDA-DMDAAC)s could be expected to bring about the covalent bonds with the hydroxyl groups of cotton (cellulose) to form an ether linkage when fixing, resulting in the stronger interactions of P(CMDA-DMDAAC)s with cotton fabric, as well as their electrostatic forces with anionic dyes to produce the insoluble-water color lakes, for the development of fastness of anionic dyes on cotton fabric.